2014
DOI: 10.1007/s00248-014-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Treatment Induces Skin Microbiota Dysbiosis and Influences Wound Healing

Abstract: Antibiotic treatment eliminates commensal bacteria and impairs mucosal innate immune defenses in the gut. However, whether oral antibiotic treatment could alter the composition of the microbiota on the skin surface and influence innate immune responses remains unclear. To test this, mice were treated with vancomycin for 7 days and then wounds were made on the back skin of the mice. Five days later, scar tissue from each mouse was collected for bacterial enumeration, the bacterial composition on the scar and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 27 publications
1
51
1
1
Order By: Relevance
“…Because prolonged and dys-regulated expression of pro-inflammatory cytokines leads to increased neutrophils influx and subsequent tissue damage, it is possible that S. epidermis derived small TLR2-activating molecules provide further host-beneficial function by dampening keratinocyte-mediated inflammation and, although wound closure kinetics and scaring has not been assessed, it might aid in reducing excessive inflammation and scaring in damaged tissue 127 . This notion is supported by the recent observation that mice administered antibiotics orally, which results in decreased bacterial density and altered microbial composition in scars by a shift in the dominating phyla from Staphylococcus to Lactobacillaceace , have decreased levels of IL-17A and RegIIIγ and experience a delay in wound healing 142 . However, germ-free mice were recently found to have faster wound healing and less scarring when compared to conventionally housed mice 143 , suggesting that although individual microbes can be host-beneficial the skin microbiota as a whole may have a negative effect on wound healing and scaring (FIG.4b).…”
Section: Microbial Tolerance and Clearancementioning
confidence: 79%
“…Because prolonged and dys-regulated expression of pro-inflammatory cytokines leads to increased neutrophils influx and subsequent tissue damage, it is possible that S. epidermis derived small TLR2-activating molecules provide further host-beneficial function by dampening keratinocyte-mediated inflammation and, although wound closure kinetics and scaring has not been assessed, it might aid in reducing excessive inflammation and scaring in damaged tissue 127 . This notion is supported by the recent observation that mice administered antibiotics orally, which results in decreased bacterial density and altered microbial composition in scars by a shift in the dominating phyla from Staphylococcus to Lactobacillaceace , have decreased levels of IL-17A and RegIIIγ and experience a delay in wound healing 142 . However, germ-free mice were recently found to have faster wound healing and less scarring when compared to conventionally housed mice 143 , suggesting that although individual microbes can be host-beneficial the skin microbiota as a whole may have a negative effect on wound healing and scaring (FIG.4b).…”
Section: Microbial Tolerance and Clearancementioning
confidence: 79%
“…We did not detect any differences in community diversity or composition due to antibiotic exposure, unlike the gut where exposure to certain antibiotics is known to decrease diversity levels, predisposing to infection by Clostridium difficile (Dethlefsen and Relman 2011; Stein et al 2013). Instead, as in other body sites (Keeney et al 2014; Modi et al 2014; Zhang et al 2014; Mayer et al 2015), antibiotics disrupted the microbiota. The extent of community disruption was not dependent on the class of antibiotic; rather it was whether the antibiotic was targeted towards the ulcer being studied.…”
Section: Discussionmentioning
confidence: 93%
“…The observed increased treatment failure among complicated appendicitis cases treated with extendedspectrum antibiotics could be related to adverse events associated with the breadth of the antibiotic spectrum (eg, Clostridium difficile infection). Lastly, experimental models have shown that microbiota changes can adversely affect gut and skin wound healing, 16,17 consistent with the association between use of microbiota-altering extended-spectrum antibiotics and postoperative complications.…”
Section: Discussionmentioning
confidence: 94%